Enhanced service differentiation using priority-based MAC protocol for MANETs. (1st January 2012) - Sarma, Nityananda; Nandi, Sukumar
MAC layer plays an important role for providing quality of service in mobile ad hoc networks. Accordingly, a real-time data frame should be provided with higher channel access priority than that of a best-effort data frame. This paper proposes a strict priority-based variant of the IEEE 802.11 DCF for QoS provision at the MAC layer of MANETs. The service differentiation is achieved by two mechanisms: a a priority-based non-overlapping contention window selection, so that smaller backoff timer values are assigned to real-time data frames to reduce their channel access delay b a priority-based queue management and packet scheduling to improve the intra-node service differentiation. Performance of the proposed scheme is investigated for single hop scenarios using a Markov chain model whose accuracy is validated through simulation. Furthermore, simulation studies in multihop scenarios show suitability of the proposed scheme to provide an enhanced level of service differentiation, especially in terms of end-to-end delay and throughput, for supporting QoS at MAC layer of MANETs.